FACTORS INFLUENCING STUDENT AND PARENT’S DECISION IN CHOOSING A SCHOOL: CASE STUDY OF SEKOLAH MENENGAH KEJURUAN SANTA THERESIA - Natalia, -; Prasetya, Wibawa (L2Dikti Wilayah III, 2020)
To enhance the quality and competitiveness of its human resource capital, in Indonesia The Sekolah Menengah Kejuruan education system is a 3 – year education system that trains the students to be ready for employment in the respective industries, as SMK Santa Theresia which offers tourism majors. The goal of this research is to identify most influential factors that affect the decision in choosing SMK Santa Theresia from parents’ and students’ perspectives, respectively. The research methods employed are the quantitative with descriptive approach, data analysis and technique summarized in multiple regression models. Furthermore, a census of 142 people has been done in order to get desired data for the analysis. Specifically, the overall demographic of the data is composed of 71 10-grade students (X PAR 1 and X PAR 2) of SMK Santa Theresia and 71 students’ parents for the academic year 2018/19. Conclusively, the results are presented from two points of view. The first, being from the students’ perspectives: it is found that reputation, image, school’s syllabus and teacher’s competence are not significant variables to influence the decision of choosing the school. Secondly, being from the parents’ perspectives: it is found that school’s syllabus is affecting decision of choosing the school.